Association of peripubertal blood lead levels with reproductive hormones and semen parameters in a longitudinal cohort of Russian men. Issue 4 (17th January 2022) - Williams, Paige L; Mínguez-Alarcón, Lidia; Korrick, Susan A; Lee, Mary M; Plaku-Alakbarova, Bora; Burns, Jane S; Smigulina, Luidmila; Dikov, Yury; Abou Ghayda, Ramy; Hauser, Russ; Sergeyev, Oleg
Abstract: STUDY QUESTION: Are peripubertal blood lead levels (BLLs) associated with semen parameters and serum reproductive hormones among young Russian men? SUMMARY ANSWER: We observed a suggestion of lower ejaculate volume with higher peripubertal BLL but no associations of BLLs with reproductive hormones measured throughout adolescence or with other sperm parameters measured at adulthood. WHAT IS KNOWN ALREADY: Lead is a known reproductive toxicant and endocrine disruptor. Previous literature has shown associations between high lead exposure and poorer semen quality both in occupationally and environmentally exposed men. However, to our knowledge, no longitudinal studies have explored the association of childhood lead exposure with semen parameters and reproductive hormones in young men. STUDY DESIGN, SIZE, DURATION: The Russian Children's Study is a prospective cohort study that enrolled 516 boys at age 8–9 years in 2003–2005 and followed them annually for 10 years. BLLs were measured at entry and lifestyle and health questionnaires were completed. Reproductive hormones were measured in blood samples collected every 2 years. PARTICIPANTS/MATERIALS, SETTING, METHODS: Among the 516 boys enrolled, 481 had BLLs measured at entry. Of these, 453 had at least one measurement of serum testosterone, follicle stimulating hormone (FSH) or luteinizing hormone (LH) (median = 5 samples per boy) and 223 had semen samples collected ∼10 years after enrolment. Semen assessment included ejaculated volume, sperm concentration, progressive motility and total sperm count, and parameters were categorized using published andrology standards for low semen quality based on sperm count and motility. Linear mixed models were used to examine the associations of log-transformed BLLs (and BLL categories) with reproductive hormones and semen parameters, adjusting for potential confounders. MAIN RESULTS AND THE ROLE OF CHANCE: Among the 223 young men with peripubertal BLLs and at least one semen sample (total samples = 438), the median (interquartile range) BLL was 3 (2, 5) µg/dl and 27% had BLL ≥5 µg/dl. Overall, 49% of the semen samples fell below reference levels for sperm count and/or motility. Men with peripubertal BLL ≥5 µg/dl had significantly lower ejaculated volume than those with BLL <5 µg/dl (mean = 2.42 vs 2.89 ml, P = 0.02), but this difference was attenuated in adjusted models (mean = 2.60 vs 2.83 ml, P = 0.25). No associations were observed between BLL measured at age 8–9 years and reproductive hormone levels or sperm parameters, including sperm concentration, total count, progressive motility and total progressive motile sperm count, or with the probability of having low semen quality based on sperm count/motility. LIMITATIONS, REASONS FOR CAUTION: Only a subset of the original cohort participated in the semen quality portion of the study, although inverse probability weighting was used to account for possible selection bias. BLLs were only measured at a single time in peripuberty, and other exposure time periods, including later or longer-term childhood exposure, may be more predictive of semen quality. The young men were also exposed to other chemical contaminants before and during pubertal development. WIDER IMPLICATIONS OF THE FINDINGS: While semen volume often receives less attention than other sperm parameters, it is an important component of male fertility. Additional prospective studies covering different exposure windows and including other seminal plasma biomarkers are warranted to explore our finding of potentially lower ejaculated volume with higher BLLs and to confirm the lack of associations for other semen parameters among youth exposed to environmental BLLs. STUDY FUNDING/COMPETING INTEREST(s): Funding was provided through grants R01ES0014370 and P30ES000002 from the National Institute of Environmental Health Sciences, grant R82943701 from the U.S. Environmental Protection Agency, and grant 18-15-00202 from the Russian Science Foundation (O.S and Y.D.). All authors report no competing interests. TRIAL REGISTRATION NUMBER: N/A.